KEBERFUNGSIAN KELUARGA ANAK KORBAN EKSPLOITASI DI KAWASAN JALAN TUANKU TAMBUSAI PEKANBARU - Maya Lestari; Tri Umari; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was conducted in the area of Jalan Tambusai Pekanbaru. Thepurpose of this study to determine the functioning of the family of children victims ofexploitation in the area of Jalan Tuanku Tambusai Pekanbaru. This research used adescriptive type of research with specified indicators, and data collecting andcalculating method with qualitative approach. to obtain the information, the researchertakes the informant in total of 9 people, they are children victims of exploitation in thearea of Jalan Tuanku Tambusai Pekanbaru. Data collection techniques in this studyusing interview techniques,and observation. After conducting this research, the resultsshowed there is no family functioning of children victims of exploitation in the area ofJalan Tuanku Tambusai, Pekanbaru.Key words: characteristics, family function, and children of exploitation victims